The multilevel inverter with clamped-diode - Trong-Thang Nguyen (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this study, the author analyzes the advantages and disadvantages of multi-level inverter compared to the traditional two-level inverter and then chose the suitable inverter. Specifically, the author analyzes and designs the three-level inverter, including the power circuit design and control circuit design. All designs are verified through the numerical simulation on Matlab. The results show that even though the three-level inverter has a low number of switches (only 12 switches), but the quality is very good: the total harmonic distortion is small; the output voltage always follows the reference voltage.